Early Detection and Prevention of Alzheimer’s Disease: Role of Oxidative Markers and Natural Antioxidants - Arslan, Jamshed; Jamshed, Humaira; Qureshi, Humaira (Frontiers in Aging Neuroscience, 2020)
Oxidative stress (OS) contributes towards Alzheimer’s disease (AD) pathology. OS can be a result of increased reactive oxygen/nitrogen species, reduced antioxidants, oxidatively damaged molecules and/or a combination of these factors. Scientific literature is scarce for the markers of OS specific for detecting AD at an early stage. The first aim of the current review is to highlight potential OS markers in the brain, cerebrospinal fluid, blood and/or urine that can be used for early diagnosis of human AD. The reason for exploring OS markers is that the proposed antioxidant therapies against AD appear to start too late to be effective. The second aim is to evaluate the evidence for natural antioxidants currently proposed to prevent or treat AD symptoms. To address these two aims, we critically evaluated the studies on humans in which various OS markers for detecting AD at an early stage were presented. Non-invasive OS markers that can detect mild cognitive impairment and AD at an early stage with greater specificity and sensitivity are primarily related to lipid peroxidation. However, a combination of OS markers, family history and other biochemical tests are needed to detect the disease early on. We also report that the long-term use of vitamins (vitamin E as in almonds) and polyphenol-rich foods (curcumin/curcuminoids of turmeric, gingko biloba, epigallocatechin-3-gallate in green tea) seem justified for ameliorating AD symptoms. Future research on humans is warranted to justify the use of natural antioxidants.